Morfoanatomia foliar de Ficus subg. Urostigma (Gasp.) Miq. (Moraceae)de ocorrência na Paraíba e revisão etnomedicinal de Ficus L. para o Brasil - Araujo, Nathalia Diniz (2012)
Ficus L., with about 750 species, is the richest of the family Moraceae, widely distributed in tropical regions of the world. The genus is characterized by lactescentes plants, woody, shrubs and lianas, often hemiepiphytes growing on tree branches or in the leaf axils of palms. In Brazil, there are about 100 species of Ficus, popularly known as "figueiras" and/or "gameleiras", many of which are exploited as sources of textiles, food and used in folk medicine. This study aimed to conduct an analysis of leaf morpho-anatomy of three species of Ficus sugb. Urostigma (Gasp.) Miq. Found in Paraíba: Ficus cyclophylla (Miq.) Miq., Ficus elliotiana S. Moore and Ficus caatingae R. M. Castro, and a review of the ethnomedicine of the species of the genus. Cross sections of leaves (blade and petiole) were performed in microtome in material embedded in methacrylate, stained with toluidine blue. The study of venation, epidermal cells, histochemical analysis and SEM were carried out using standard methods for each analysis. A review of the ethnomedicine of Ficus was performed, through literature search and various databases. The three species share the following characters: dorsiventral mesophyll, collateral vascularization, the presence of cytoplasmic inclusions of druses and prismatic crystals type (distributed in all tissues of the leaf), angular collenchyma, epidermis with straight polygonal anticlinal walls, hypostomatic and anomocytic stomata. They have characters that distinguish them from their related species, particularly with respect to the structural organization of the mesophyll, board, border and vascularization of the petiole. With respect to etnomedicinal revision, 27 species were reported (23.3%) used in traditional medicine in Brazil. Among the most common therapeutic indications, the most important were those reported for the digestive system and against intestinal worms (29%). The plant parts are used more sheets (63%), followed by the use of latex (51.8%). The oral use was the main route of administration (72.7%). Leaf anatomy was more relevant than the external morphology and can be used for the characterization of the three species and to support quality control of his herbal drugs, as it provided for the same distinctive characters. In addition, the survey provided the record etnomedicinal plants with popular uses that can serve as a basis for the election of species that can be employed as a source of biologically active compounds.